Maternal environmental noise exposure during the periconceptional period and risk of congenital heart disease in offspring: a case-control study in Northwest China - Mingxin Yan; Yan Zhao; Yunbo Zhang; Doudou Zhao; Bin Wang; Jianting Si; Yuanhan Sun; Guoqiang Dong; Leilei Pei; Pengfei Qu (Frontiers in Public Health, 2026)
Background Environmental noise is a pervasive public health concern, yet evidence linking maternal environmental noise exposure during the periconceptional period to the risk of congenital heart disease (CHD) in offspring remains limited, particularly in low and middle-income settings. Methods We conducted a multicenter hospital-based case-control study in Xi’an, Northwest China, including 589 mothers of infants with CHD and 1193 frequency-matched controls. Maternal periconceptional noise exposure was assessed using standardized questionnaires, capturing exposure duration, perceived interference, and dominant noise sources (traffic, construction, and industrial). Multivariable logistic regression estimated odds ratios (ORs) and 95% CIs, adjusting for potential confounders. Restricted cubic spline analysis assessed nonlinear exposure–response relationships. Results Maternal periconceptional noise exposure was associated with increased CHD risk (OR, 1.81; 95% CI, 1.36–2.40). Compared with no noise exposure, exposure for 4 to ≤8 hours per day was associated with higher risk (OR, 3.24; 95% CI, 2.02–5.20), as was exposure for more than 8 hours per day (OR, 2.07; 95% CI, 1.19–3.58). Traffic noise (OR, 1.75; 95% CI, 1.20–2.56) and construction and industrial noise (OR, 2.13; 95% CI, 1.29–3.50) were also independently associated with increased risk. Restricted cubic spline analysis indicated a positive nonlinear association between noise exposure duration and CHD risk. Conclusion Maternal periconceptional exposure to environmental noise was associated with increased CHD risk in offspring, particularly with prolonged exposure and specific sources such as traffic and construction. Reducing environmental noise exposure during the periconceptional period may be important for CHD prevention.